Estimation of prevalence of dengue viral infection among clinically suspected patients attending a tertiary care centre in Uttar Pradesh, India - Kumar, Amit; Kanaujia, Rachana; Bajpai, Malay (International Journal of Advances in Medicine, 2020)
Background: Dengue virus infection is fastest spreading, mosquito borne viral disease in the world with an estimated 3.9 billion people at risk of infection. Dengue is notifiable disease in India, but real number of cases could not be identified many times due to the under-reporting or misdiagnosis of cases. The purpose of the present study was to estimate prevalence of dengue viral Infection among suspected patients attending a tertiary care centre. Methods: Blood samples from suspected patients were collected over a period of 1 year and were analysed for dengue virus specific IgM antibodies and NS1 antigen by immuno-chromatographic method. Results: Total 196 samples were tested out of which 43 (21.43%) showed laboratory evidence of dengue. Maximum samples were received during monsoon and post-monsoon period. Dengue sero-positivity was found to be highest in post monsoon period i.e., October-November. Maximum dengue positivity rate was found in the age group of 16-45 years. Conclusions: For estimation of true burden of dengue in India and its geographical mapping to control further disease transmission; laboratory-based active surveillance systems are required along with passive surveillance and control programs.